2017
DOI: 10.1074/jbc.m116.757039
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for the Lesion-scanning Mechanism of the MutY DNA Glycosylase

Abstract: Edited by Patrick SungThe highly mutagenic A:8-oxoguanine (oxoG) base pair is generated mainly by misreplication of the C:oxoG base pair, the oxidation product of the C:G base pair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 41 publications
2
30
0
Order By: Relevance
“…The subsequent transitions starting from the S2 state involve the compression of the DNA backbone and eversion of the target nt into the active site, which are also actively promoted by TDG. The active role of other DNA repair/modify proteins in promoting the base flipping have also been demonstrated by former biochemical or crystallographic studies ( 40 , 45 , 48 , 63 , 64 , 111 ). For example, the key intercalation residues, e.g.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…The subsequent transitions starting from the S2 state involve the compression of the DNA backbone and eversion of the target nt into the active site, which are also actively promoted by TDG. The active role of other DNA repair/modify proteins in promoting the base flipping have also been demonstrated by former biochemical or crystallographic studies ( 40 , 45 , 48 , 63 , 64 , 111 ). For example, the key intercalation residues, e.g.…”
Section: Discussionmentioning
confidence: 70%
“…Whether the repair enzyme actively promotes the base-flipping or passively traps the extrahelical nt has been a subject of many structural ( 39 , 40 , 63 ), biochemical ( 48 ), NMR ( 23 ) and single-molecule studies ( 47 , 51 , 66 ). One way to answer this question is to directly compare the flipping rate of the damaged nt with and without protein binding, as evidenced by previous imino proton exchange assay for UDG ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparing this structure to that of full-length MutY bound to lesion-containing DNA suggested that a loop region of the C-terminal domain may be in proximity to interact with OG:A from the major groove side. 35 Due to the known role of the CTD in OG recognition, 13,20,34,3638 and its required presence for cellular repair of OG:A mismatches, 20,39 the idea that this CTD loop region could be important for OG syn recognition via interactions with the 2-amino group is appealing. Indeed, these recognition features could involve direct hydrogen-bonding or steric interactions that aid in stalling MutY as it moves along DNA.…”
Section: Resultsmentioning
confidence: 99%